The Relationship between Obsessive Compulsive Personality and Obsessive Compulsive Disorder Treatment Outcomes: Predictive Utility and Clinically Significant Change - Sadri, S.; McEvoy, Peter; Egan, S.; Kane, R.; Rees, Clare; Anderson, R. (Cambridge University Press, 2017)
Background: The evidence regarding whether co-morbid obsessive compulsive personality disorder (OCPD) is associated with treatment outcomes in obsessive compulsive disorder (OCD) is mixed, with some research indicating that OCPD is associated with poorer response, and some showing that it is associated with improved response. Aims: We sought to explore the role of OCPD diagnosis and the personality domain of conscientiousness on treatment outcomes for exposure and response prevention for OCD. Method: The impact of co-morbid OCPD and conscientiousness on treatment outcomes was examined in a clinical sample of 46 participants with OCD. Results: OCPD diagnosis and scores on conscientiousness were not associated with poorer post-treatment OCD severity, as indexed by Yale-Brown Obsessive Compulsive Scale (YBOCS) scores, although the relative sample size of OCPD was small and thus generalizability is limited. Conclusion: This study found no evidence that OCPD or conscientiousness were associated with treatment outcomes for OCD. Further research with larger clinical samples is required.